PERSELINGKUHAN DAN AKIBAT HUKUM DALAM PERSPEKTIF HUKUM ADAT ROON DI YENDE TELUK WONDAMA - Billy Andre Tohatta; Prisilia Waropen; Wellem Hendra Balubun (Fakultas Hukum, Universitas Caritas Indonesia, 2025)
The aim of the research is to determine the causes of infidelity and the legal consequences from the Perspective of Roon Customary Law in Yende, Teluk Wondama and to determine the Application of Sanctions to the Two Parties Who Have an Affair in the Perspective of Roon Customary Law in Yende, Teluk Wondama.This research was conducted empirically. Data sources obtained using primary data and secondary data. Data collection procedures were carried out by means of literature study and field research. Data analysis used in this research uses qualitative analysisThe research results show that (1) Factors that influence the occurrence of infidelity include disappointment, dissatisfaction in sexual life, insufficient financial needs, closeness to other friends, the influence of close friends, social media factors and the legal consequences of infidelity from Roon's Customary Law Perspective in Yende, Wondama Bay is given a customary sanction in the form of a customary fine which must be paid by the perpetrator of the affair (2) In the implementation of the customary sanction for the perpetrator of the affair, it is processed according to the customary law that applies in the Roon tribal community, namely by procedures that have been regulated by the Traditional Head (mananir) namely by holding a customary trial by paying customary fines in the form of babyak Rowena (goods), namely plates (Rosaser), sago trees (Ai Ran), boats (Wa). Apart from that, the party who commits the affair is also obliged to pay a customary fine to both families of the party who committed the affair, which is called paying shame money (pipi wewak mamuai) so that there is justice for both families of the perpetrator of the affair.